2002
DOI: 10.1046/j.1365-2125.2002.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐finding and efficacy study for i.m. artemotil (beta‐arteether) and comparison with i.m. artemether in acute uncomplicated P. falciparum malaria

Abstract: Aims The antimalarial efficacy/pharmacodynamics and pharmacokinetics of intramuscular (i.m.) artemotil in Thai patients with acute uncomplicated falciparum malaria were studied to determine effective dose regimens and to compare these with the standard dose regimen of artemether. Methods In part I of the study three different artemotil dose regimens were explored in three groups of 6-9 patients for dose finding: 3.2 mg kg x1 on day 0 and 1.6 mg kg x1 on days 1-4 (treatment A), 1.6 mg kg x1 on day 0 and 0.8 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The rate of absorption of the injected drug from the oil depot may be influenced by the oil itself. Recent studies comparing artemether and arteether absorption indicated even slower absorption of arteether injected in sesame seed oil (8). Use of alternative oils to dissolve these lipophilic drugs may accelerate absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of absorption of the injected drug from the oil depot may be influenced by the oil itself. Recent studies comparing artemether and arteether absorption indicated even slower absorption of arteether injected in sesame seed oil (8). Use of alternative oils to dissolve these lipophilic drugs may accelerate absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Precise oral dosing was provided by taking the powder from 40-mg artemether capsules (Kunming Pharmaceutical Factory), weighing it, and replacing the weight-adjusted amount back in the capsule. Blood samples were taken through an indwelling forearm vein catheter at 0, 15, 30, 45, 60, 90, and 120 min and then 3,4,6,8,12,18, and 24 h following drug administration. A second dose of artemether (2 mg/kg) was then given at 24 h by the alternative route.…”
Section: Methodsmentioning
confidence: 99%
“…The rates of recrudescence, fever, and parasite clearances are traditional parameters for the efficacy of the antimalarial drugs in humans. These parameters exhibit the therapeutic potential of intramuscular arteether (AE) with sesame oil (Artemotil), which has much less efficacy [3,4] compared to that of intramuscular artemether (AM) [5][6][7][8][9][10][11][12][13], oral and intravenous artesunate (AS) [2,14], and the oral dihydroartemisinin (DHA) [15][16][17][18] or even than that of intramuscular / -arteether formulated with peanut oil [19][20][21][22] in India. It is clear that the efficacy and recrudescence in humans are dissimilar along those clinical trials with different artemisinin drugs by the monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…3 The recommended treatment for cerebral malaria is quinine by slow intravenous infusion. 4 However, quinine has several drawbacks, including a short half-life, painful local reactions after intramuscular and intravenous administration 5 and neurotoxicity. 5,6 Permanent blindness with standard doses of quinine has been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, quinine has several drawbacks, including a short half-life, painful local reactions after intramuscular and intravenous administration 5 and neurotoxicity. 5,6 Permanent blindness with standard doses of quinine has been well documented. 6 Furthermore, decreasing sensitivity to quinine has been reported in south-eastern Asia and the Amazon region, 7 as well as in parts of Africa.…”
Section: Introductionmentioning
confidence: 99%